2011
DOI: 10.1016/j.humov.2010.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcaneal eversion on three-dimensional kinematics of the hip, pelvis and thorax in unilateral weight bearing

Abstract: Understanding the kinematic chain from foot to thorax will provide a better basis for assessment of malalignment of the body. The purpose of this study was to investigate the effects of induced calcaneal eversion on the kinematics of the hip, pelvis and thorax in three dimensions under unilateral weight-bearing. Twenty-eight healthy males were requested to stand on one leg under three conditions: normal (standing directly on the floor), and on wedges producing 5° and 10° calcaneal eversion. Recorded kinematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
3
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 21 publications
5
53
3
6
Order By: Relevance
“…With use of a wedge to keep the foot fixed in inversion and eversion, a research was done to observe the changes in the body. Although the results were not found to be statistically significant in the amount of pelvic tilt, a decreasing trend was confirmed [9]. In a study with a wedge placed in the front, rear, medial and lateral sides to compare the movements of the leg, the subtalar joint moved 6 times more with a wedge placed in the medial and rear than without use of a wedge, and with a wedge on the medial and rear in the sagittal plane, the ankle and hip joint angles in the frontal plane, the trunk movement moves 2-3 times more than without use of a wedge [10].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…With use of a wedge to keep the foot fixed in inversion and eversion, a research was done to observe the changes in the body. Although the results were not found to be statistically significant in the amount of pelvic tilt, a decreasing trend was confirmed [9]. In a study with a wedge placed in the front, rear, medial and lateral sides to compare the movements of the leg, the subtalar joint moved 6 times more with a wedge placed in the medial and rear than without use of a wedge, and with a wedge on the medial and rear in the sagittal plane, the ankle and hip joint angles in the frontal plane, the trunk movement moves 2-3 times more than without use of a wedge [10].…”
Section: Introductionmentioning
confidence: 63%
“…A study by Khamis et al [13] had found the following results of the measurements with changes in alignment from In a previous study using a fixed wedge, the pelvis was tested for associated correlation with other LE structures. With use of the wedge and heel abducted, the hip abduction angle and pelvic anterior tilt increased [3,9]. Eslami et al [10] completed a study using a foot wedge to observe the pelvis and trunk angle variability during single-limb stance and found the anterior tilt in the horizontal plane to have a change in 0.052 o , however was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are patient reports of people with knee disorders due to pes valgus and related restrictions in tarso-metatarsal joint movement [3]. There is additional evidence that muscle weakness in the hips and related movement patterns can have a negative impact on the biomechanics of the knee joint [4,5]. …”
Section: Knee Complaintsmentioning
confidence: 99%
“…All patients were given (physio)therapy based on the common Spiraldynamik ® therapeutic approach [5]. A total of 48 patients with knee disorders were analyzed (mean age: 52.7 years, min: 19 year, max: 89 year).…”
Section: Patient Populationmentioning
confidence: 99%